Simultaneous observations of transionospheric and HF ionospheric propagation within the polar cap. Issue 5 (3rd October 2013) - Siddle, D. R.; Stocker, A. J.; Warrington, E. M.; Zaalov, N. Y.; Homam, M. J.
Abstract [1] The total electron content of the ionosphere over Alert, Canada was measured continuously for over 3 years using a dual frequency GPS receiver. Peaks in the measured total electron content are attributed to the presence of convecting polar patches (patches of enhanced ionization), which increase in number and intensity with increasing sunspot number, peaking in October to November 2011. In addition, HF radio transmissions were made at frequencies between 4 and 14 MHz over a path from Qaanaaq, Greenland to Ny‐Ålesund, Svalbard and several examples are presented in which features in the received signals are visible by these two means almost simultaneously. The reception of the higher‐frequency transmissions is shown to be dependent on the presence of polar patches.